DEVELOPMENT OF ANDROID-BASED DIMENSI APPLICATION AS A MEDIA FOR POETRY WRITING SKILLS FOR ELEMENTARY SCHOOL STUNDENTS - Adisa Adriani; Dadan Djuanda; Prana Dwija Iswara (Universitas Majalengka, 2024)
This research is motivated by the use of less than optimal media in Indonesian language learning, especially poetry material. This is because of the lack of creativity of teachers in utilizing technology and learning is only centered on textbooks so that students find it difficult to understand the learning materials delivered by teachers. The purpose of this research is to develop learning media in the form of an Android-based application